Effect of phosphate-solubilizing bacteria on growth and yield of Arachis hypogaea L. in varied soil types - Suhartono, Suhartono; Suryono, Edy; Yusriah, Yusriah; Khoiri, Syaiful (Agrovigor, 2023)
Peanut (Arachis hypogaea L.) is widely cultivated both in monoculture and polyculture (usually with corn) on dry land in Madura. Generally, the soil types of Madura are grumusol, regosol, and mediterranean. These three types of soil each have different physical and chemical properties. The effect of the addition of phosphate-solubilizing bacteria on the three soil types is unknown. The study aimed to determine the response of peanut plant growth due to the addition of phosphate solubilizing bacteria, Pseudomonas fluorescens, in three different soil types. The research was conducted in the experimental garden of Agroecotechnology, Faculty of Agriculture, Universitas Trunojoyo Madura. The research design used a non-factorial completely randomized design (CRD) with six treatments and four replications. The treatment consisted of three types of soil, namely regosol, grumosol, and mediteran as well as with and without the addition of P. fluorescens. The results showed that the treatment had a significant effect on the parameters of plant height, number of leaves, number of pods, pod dry weight, seed weight, above-ground biomass, root dry weight, and plant P content. The treatment did not show a significant effect on the root-canopy ratio and P. fluorescens population parameters.